DEVELOPMENT AND IMPLEMENTATION OF VIRTUAL EXTRACTION LABORATORY IN BUILDING HIGH-LEVEL THINKING SKILLS (HOTS) TO IMPROVE LEARNING OUTCOMES. - Juita Febiola Napitupulu (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lampung, 2025)
Development and Implementation of Virtual Extraction Laboratory in Building High-Level Thinking Skills (HOTS) to Improve Learning Outcomes. This study aimed to develop and implement a virtual laboratory media on the topic of extraction to enhance higher order thinking skills (HOTS) and improve students' learning outcomes. The research used a Research and Development (R&D) approach with the 4D model (Define, Design, Develop, Disseminate). The subjects were two classes of chemistry education students: an experimental group using the virtual laboratory and a control group using conventional methods. Instruments included a learning achievement test, expert validation questionnaires, student response questionnaires, and a HOTS rubric. Results showed the media was highly feasible, with an N-Gain score of 0.74 (high category) for the experimental group and an average HOTS score of 90.53 (very high category). It can be concluded that the virtual laboratory is effective in improving learning outcomes and developing students' higher order thinking skills.